Design of a Water System Monitoring and Seawater Quality Study at the Floating Dock of PT PAL Indonesia - Pratama, Adika; Amalia, Aussie (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2025)
As ship repair and maintenance activities increase in the floating dock area of PT PAL Indonesia, they consequently affect the surrounding seawater quality. However, at present, the determination of seawater pollution levels is still conducted through manual sampling followed by laboratory analysis, which requires a considerable amount of time. Therefore, an IoT-based seawater quality monitoring system is proposed as a solution to this problem. The objectives of this study were to determine the level of seawater pollution in the floating dock area and to analyze the relationship between independent variables and the dependent variable. This study employed a quantitative research method consisting of three stages: first, the design and assembly of the monitoring device; second, sampling at each predetermined location; and third, correlation testing to determine the relationship between independent variables and the dependent variable using the Pearson correlation method. The results showed that the average values of pH, temperature, turbidity, salinity, and dissolved oxygen were 7.04, 27.60 °C, 4.88 NTU, 32.25 ‰, and 8.25 ppm, respectively. The study concludes that the seawater quality in the floating dock area still meets the seawater quality standards in accordance with the Decree of the Minister of Environment of the Republic of Indonesia Number 51 of 2004, and that there are two independent variables that are significantly correlated with the dependent variable.